'Crânement beau tout de même': still life and Le Ventre de Paris - Tunstall, K (Oxford University Press, 2004)
This essay revisits the relationship between Zola's descriptive techniques and painting by taking a detailed look at Le Ventre de Paris, and at one particular genre of painting, still life. The argument involves dissolving the easy identification between the painter Claude Lantier and the narrator in order to reveal the presence of visions of Les Halles other than Claude's quasi-Impressionist one, to which much critical attention has been devoted. In a series of close readings of the visual descriptions, this essay reveals the presence of a Rococo aesthetic, implying parallels between the Second Empire and the eighteenth century; by exploring Florent's perspective on Les Halles in particular, it uncovers vanitas imagery and memento mori in which 'nourriture' is 'pourriture'. To read Le Ventre de Paris is thus to be placed in a position analogous to that of the spectator in Holbein's The Ambassadors, with its notorious anamorphosis; for, as the narrative perspective shifts between Claude and Florent, and as the descriptions evoke Impressionist, Rococo and early modern aesthetics, so the death's head flickers disconcertingly in and out of view.